2014
DOI: 10.5433/1679-0359.2014v35n2p625
|View full text |Cite
|
Sign up to set email alerts
|

Necessidades hídricas da cana-de-açúcar cultivada em clima tropical

Abstract: ResumoA estimativa precisa do consumo hídrico da cana-de-açucar é importante para obtenção da máxima produtividade com menos investimentos. O objetivo do trabalho foi determinar as necessidades hídricas da cana-de-açúcar cultivada em clima tropical. O experimento foi realizado no Estado da Paraíba, durante o ciclo produtivo da cultura da cana-de-açucar variedade RB 92 579 irrigada por pivô central, no período de outubro de 2009 a setembro de 2011. A evapotranspiração da cultura (ETc) foi obtido pelo método do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
0
6
0
2
Order By: Relevance
“…According to Silva et al (2012), mean daily evapotranspiration for sugarcane crop in the semi-arid region of the São Francisco river valley, Brazil, is 4.7 mm day -1270 1 . In another study in the same region, Silva et al (2014b) found sugarcane evapotranspiration of 4.3 mm day -1 . In the irrigated treatments, 360 mm were applied in 12 events of 30 mm (Fig 3).…”
Section: Climate Conditionsmentioning
confidence: 83%
“…According to Silva et al (2012), mean daily evapotranspiration for sugarcane crop in the semi-arid region of the São Francisco river valley, Brazil, is 4.7 mm day -1270 1 . In another study in the same region, Silva et al (2014b) found sugarcane evapotranspiration of 4.3 mm day -1 . In the irrigated treatments, 360 mm were applied in 12 events of 30 mm (Fig 3).…”
Section: Climate Conditionsmentioning
confidence: 83%
“…Este processo quando não reversível, de acordo com o mesmo autor, interfere significativamente nas reações secundárias da fotossíntese e diminuindo a produtividade de biomassa. O fato de todos modelos terem sido lineares demonstra que a planta ainda responder a valores mais altos de reposição de água via irrigação, com o uso de valores maiores de coeficiente da cultura (kc), como observado por Silva et al (2014), onde concluíram que os valores do coeficiente de cultivo propostos pela FAO para a cultura da cana-de-açúcar não são apropriados para regiões tropicais.…”
Section: Resultsunclassified
“…These authors also pointed out the importance of conducting in situ studies to calibrate crop coefficients. Silva et al (2014) proved FAO Kc for sugarcane to be inappropriate for tropical regions, being required an adjustment for its suitability. By contrast, Rios et al (2011) estimated Kc values of castor beans for growth, vegetative growth, fruiting, and maturation phases within FAO-56 limits and recommendations.…”
Section: Resultsmentioning
confidence: 99%